2021
DOI: 10.15421/022158
|View full text |Cite
|
Sign up to set email alerts
|

Serum clinical biochemical markers of Hy-Line W-36 laying hens under the influence of increased stocking densities in cages of multilevel batteries

Abstract: Today, the organism of hens is constantly exposed to numerous technological stressors in the conditions of industrial poultry farming, the least studied of which are long-term, which can cause the development of chronic stress. One of such stressors is the increased stocking density of hens, which is also a way of saving resources in egg poultry and is often used by producers to obtain more eggs per 1 m2 of poultry area. The aim of this study was to examine the effect of overcrowding, as a factor of chronic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The blood RBC, HGB, and HCT levels of chickens fed with Sihuang in the SH group increased, which improved the body's nutrient and oxygen transport capacity, and had a positive effect on the body's recovery. Under today's intensive and industrialized poultry production model, environmental stress will be an important cause of poultry intestinal and liver tissue damage [25][26][27]. The results of this study showed that feeding Sihuang significantly reduced the activities of ALT and AST enzymes in chicken serum, and could stabilize the ALT enzyme activities at the same level as in the CON group.…”
Section: Discussionmentioning
confidence: 65%
“…The blood RBC, HGB, and HCT levels of chickens fed with Sihuang in the SH group increased, which improved the body's nutrient and oxygen transport capacity, and had a positive effect on the body's recovery. Under today's intensive and industrialized poultry production model, environmental stress will be an important cause of poultry intestinal and liver tissue damage [25][26][27]. The results of this study showed that feeding Sihuang significantly reduced the activities of ALT and AST enzymes in chicken serum, and could stabilize the ALT enzyme activities at the same level as in the CON group.…”
Section: Discussionmentioning
confidence: 65%
“…The preservation of hens' livestock in all groups, regardless of the light wavelength parameters, was lower than the level (97.4%) recommended by the company by the cross developer of (Guide to the content of the final hybrid Hy-Line W-36, 2019), which may be related to the peculiarities of keeping large numbers of birds in multi-tiered cage batteries of new structures (Sakhatsky et al 2020;Osadcha et al 2021). As a result, a decrease in the hens' preservation was observed with a decrease in the length of the light wave (Table 4).…”
Section: Resultsmentioning
confidence: 77%
“…Therefore, the actual area of research in poultry farming is the search for informative systems for early diagnosis of stress development in laying hens, as a precursor to reduced productivity. Several cytological techniques (Lee et al, 2022) and humoral approaches (Osadcha et al, 2021) have already been used to diagnose stress. However, they have substantial drawbacks: cytological methods have a long-hidden period, caused by the accumulation of appropriate cellular elements in the blood, and humoral methods are rather expensive and resource-intensive.…”
Section: Discussionmentioning
confidence: 99%